The Role of Regional Institutions in Sustainable Development: A Review of the Mekong River Commission First 15 Years - Ha, Mai-Lan (Consilience, 2011)
The implementation of sustainable development principles often comes into conflict with government driven needs for greater economic growth. The richly diverse Mekong Region–which comprises the six riparian nations of China, Burma, Laos, Thailand, Cambodia, and Vietnam–is in the midst of a regional debate between development and ecological preservation. The Mekong River Commission (MRC), the sole organization in the region tasked with managing this delicate balance, is struggling to find a balance between utilizing the Mekong’s waterways for economic growth without undermining the vitality of the river for use by future generations. In its 15 year history, the organization has never truly defined its basic principles on sustainability and has instead shifted positions as its leadership has changed. The MRC is also trapped in a difficult balance with its upstream neighbors; due to its limited authority, the MRC has been unable to effectively manage water usage and development along the Mekong region.